2014
DOI: 10.1016/j.exer.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profile of cellular senescence-related genes in Fuchs endothelial corneal dystrophy

Abstract: Fuchs endothelial corneal dystrophy (FECD) is a genetically heterogeneous disease. Hypothesizing that cellular senescence may be relevant in FECD pathogenesis, genetically undifferentiated late-onset FECD endothelial samples were analyzed to identify common changes of specific senescence-related transcripts. Total RNA was extracted from 21 FECD endothelial samples retrieved from patients undergoing lamellar keratoplasty due to clinically diagnosed end-stage FECD and from 12 endothelial samples retrieved from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 27 publications
2
25
1
Order By: Relevance
“…Exposure of normal corneal endothelial cells to oxidative stress results in a loss of proliferative capacity and reduced cellular function [51]. Furthermore, increased expression of cellular senescence-related genes has been observed in tissue from FECD patients [52]. Intriguingly, our finding of promoter DNA hypermethylation of genes involved in cellular metabolism is consistent with a prior serial analysis of gene expression (SAGE) study that compared gene expression profiles of normal human CE with Fuchs’ CE [35].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of normal corneal endothelial cells to oxidative stress results in a loss of proliferative capacity and reduced cellular function [51]. Furthermore, increased expression of cellular senescence-related genes has been observed in tissue from FECD patients [52]. Intriguingly, our finding of promoter DNA hypermethylation of genes involved in cellular metabolism is consistent with a prior serial analysis of gene expression (SAGE) study that compared gene expression profiles of normal human CE with Fuchs’ CE [35].…”
Section: Discussionmentioning
confidence: 99%
“…In the cornea, the senescence of epithelial and endothelial cells has been reported in human samples, animal models, and cultured cells. 40,[49][50][51] To explore whether senescent cells commonly occur in the stroma after corneal injury, we further established corneal scarring, alkali burn, and PKP mouse models. The whole-mount and section staining showed that the SA-b-galþ cells accumulated in the corneal stroma, with varied numbers and locations in different models (Figs.…”
Section: Presence Of Senescent Cells In Multiple Corneal Injury Modelsmentioning
confidence: 99%
“…The lack of Fuchs corneal dystrophy in PTHS patients that have heterozygous loss-of-function E2-2 mutations, suggests that Fuchs corneal dystrophy might involve E2-2 gain-of-function. Interestingly, endothelial samples from Fuchs corneal dystrophy patients exhibit reduced ID1 expression, which could be another route to elevate E2-2 activity (Matthaei et al, 2014)(Figure 1). Since corneal endothelium is normally non-proliferative, cell cycle arrest is unlikely to cause disease, but altered expression of senescence-related genes has been reported (Matthaei et al, 2014).…”
Section: Fuchs Corneal Dystrophymentioning
confidence: 99%
“…Interestingly, endothelial samples from Fuchs corneal dystrophy patients exhibit reduced ID1 expression, which could be another route to elevate E2-2 activity (Matthaei et al, 2014)(Figure 1). Since corneal endothelium is normally non-proliferative, cell cycle arrest is unlikely to cause disease, but altered expression of senescence-related genes has been reported (Matthaei et al, 2014). In Drosophila , elevated Da expression can be toxic and activates the Salvador-Warts-Hippo pathway of tumor suppressors (Wang and Baker, 2015), but it is not known whether this occurs in Fuchs corneal dystrophy.…”
Section: Fuchs Corneal Dystrophymentioning
confidence: 99%